Living Longer and Healthier in "Blue Zones": What Conclusions Can We Draw from This? - Doepp, Manfred (British Journal of Healthcare and Medical Research, 2025)
The existence of "blue zones" in the form of islands is as indisputable as the better health and higher life expectancy found there. The living conditions of the inhabitants there are well known; they contrast with today’s stressful and unnatural life in a big city. Here we consider the extent to which the sea, the waves, the surf, the spray and the sandy beach can have a positive effect via excited electrons, the piezo effect and singlet oxygen. Parallels are drawn with the well-known waterfall effect/balloelectricity. The conclusion is that these effects should be incorporated into life as far as possible.